(untitled) (Eurasian Research Bulletin, 2026)
This scientific article systematically and consistently covers the theoretical foundations, content and essence of vocational guidance of students, as well as pedagogical mechanisms for its effective organization. It also substantiates the role of diagnostic, motivational, information-educational, activity-orienting and reflexive mechanisms in identifying students’ professional interests and abilities, and guiding them to a conscious choice of profession. The issues of increasing the effectiveness of vocational guidance based on a competency-based approach and innovative and digital technologies in the modern education system are also analyzed.